Administrative reform in India: retaining the British steel frame. Issue 3 (2nd September 2018) - Masum, Noor Mohammad
ABSTRACT: This study analyses administrative reforms in India to identify the philosophical, cultural and ideological underpinnings of these reforms and their impacts. The study hypothesizes that despite differences in state ideologies, Indian leaders have followed the 'democratic incremental approach of reform', which has contributed significantly in achieving the continuity of the bureaucracy and ongoing development in India. There has been continuity in diverse administrative legacies in India. Muslim and British rulers modernized the ancient Indian district administration to serve their purposes while independent India takes pride in the revival of its ancient legacy. Before British rule, Indian rulers—Muslims and Hindus—maintained a semi-retainer bureaucracy; whereas the British adopted the philosophy of a mandarin bureaucracy. After independence, India replaced the British administrative philosophy of a mandarin bureaucracy with 'the democratic philosophy of a semi-retainer bureaucracy'. Influenced by this philosophy, Indian leaders retained the inherited steel frame and made only incremental changes. As a result, Indian bureaucracy remains almost as strong as it was during the British era in terms of structural and procedural perspectives. Overall, the bureaucracy is still performing reasonably well in maintaining continuity of administration and, in the process, cultural integration of society, ongoing economic development and political stability in India.